Stratégies des Premiers Peuples au Canada concernant les données numériques : décolonisation et souveraineté - Karine GENTELET; Alexandra BAHARY-DIONNE (Tic & Société)
In this paper, we propose a reflection from a position of allies on the issues of decolonization of information and data sovereignty. Given the increasing use of digital data by a plurality of actors, we aim to contribute to the reflections on digital governance by linking the latter to a number of informational issues that First Peoples in Canada are facing. We present various observations that we believe would support the idea that First Peoples’ digital strategies that are based on traditional epistemologies and informational control structures would make it possible to implement a decolonized governance of the digital data that concerns them. As such, it would then reflect the digital agency of First Peoples.